Effective interaction Potentials in H-He Plasmas - Амиров, С.М.; Рамазанов, Т.С.; Молдабеков, Ж.М. (Recent Contributions to Physics, 2016)
This paper presents an effective interaction potentials for pairs of e–He, e–He+, p–He, p–He+, taking into account influence of quantum effects of diffraction, and screening . Screening effect is taken into account within random phase approximation. To account for the quantum diffraction effect, we take the quantum Deutsch potential. The equations of effective interaction potentials for the electron (proton) – He and an electron (proton) – He+ pairs for various plasma parameters. In order to construct the total pair interaction potential, it is necessary to add the pair potentials obtained in this paper to the polarization potential and the potential caused by the quantum exchange effect.